Edukasi Gizi Seimbang Pada Remaja Di Wilayah BTN Pagesangan Pepabri Melalui Penggunaan Aplikasi Deteksi Dini Dan Edukasi Potensi Obesitas - Risa Arieska (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
Population health is influenced by nutritional intake in the food consumed. In accordance with the SDGs goal, eliminating hunger, people's nutrition must be considered. Each person's nutritional adequacy rate varies depending on gender, age, level of physical activity, and physiological condition. Adequate nutrition or excess nutritional consumption is related to obesity. Obesity is a serious public health problem throughout the world. One of the activities that can be carried out to fulfill education regarding the fulfillment of balanced nutritional health is by obtaining information through interactive lecture-based counseling or using smartphone applications. The Method is Counseling using an application for early detection of potential obesity seeks to provide knowledge to teenagers regarding balanced nutrition education, starting with coordination with the Head of RT 5, outreach with posyandu cadres, counseling for RT 5 teenagers and evaluation of activities. The results of the evaluation of this activity are an increase in teenagers' knowledge regarding balanced nutrition and they are more aware of their condition, motivated to be more active in exploring information regarding the fulfillment of balanced nutrition. The Conclusion is Access and quality of health services for adolescents regarding nutritional health status is carried out by assessing the standards for fulfilling balanced nutrition with status categories based on body mass index. Access can be achieved through various media, one of which is a smartphone-based application